TESTING POSSIBILITY OF ESTABLISHING CREDITWORTHINESS OF SMALL AND MEDIUM ENTERPRISES IN BOSNIA AND HERZEGOVINA BY APPLYING KRALICEK DF INDICATOR - Arijana Salkić (Economic Review, 2013)
Banks in Bosnia and Herzegovina are exposed to credit risk the most, since loans make up the largest part of the total banking assets. The need to improve the decision-making process in credit business in banks in Bosnia and Herzegovina is confirmed by a rapid trend of participation of non-performing loans, especially loans to legal entities. The growth of low-quality assets results in a significant increase in bank reserves, which is further reflected in the achievement of their business results. In accordance with the foregoing, it is evident that the credit risk is dominant in banking business in Bosnia and Herzegovina, and that the reduction of credit risk to a level acceptable to a bank is crucial to its survival on the market and its successful business results. Kralicek discriminant function is a model for the assessment of financial stability and solvency of companies. This model was developed based on sample of European companies, and it contains several key indicators, each of them of a corresponding weight. The assumption is that the financial indicators of failed companies, which have problems in business and orderly settlement of obligations, are different from the financial indicators of successful, financially healthy companies. In this paper we present the basic aspects of Kralicek discriminant function and test the possibility of its application to establish the creditworthiness of small and medium companies in Bosnia and Herzegovina. Kralicek DF indicator is used to determine the financial stability of two groups of companies: companies with the orderly repayment of credit obligations and enterprises with the delay in repayment longer than 90 days. We calculated the success of the model for properly categorized companies (the percentage of correct classification for companies that regularly settle their debt, for default companies and the overall average). The obtained results are presented and analyzed and appropriate conclusions and recommendations for future research have been made.